Efficient synthesis method of ethyl 3-ethoxypropionate
Through the design of the modified UiO-66 catalyst and the preparation of multiple process steps, the problems of difficult catalyst recovery, low activity, many by-products and low purity in the existing 3-ethoxypropionate synthesis method are solved, and efficient and low-cost 3-ethoxypropionate synthesis are achieved.
Patent Information
- Application Number
- CN202510129349.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-05
- Publication Date
- 2025-03-04
AI Technical Summary
The existing synthesis method of ethyl 3-ethoxypropionate has problems such as difficulty in recovering catalysts, low activity, many by-products, and low purity, and is relatively expensive.
The modified UiO-66 catalyst is prepared through multiple process steps, including ultrasonic dispersion, hydrothermal reaction, spray drying, etc., to form a catalyst with a high specific surface area and rich catalytic active sites, and through specific reaction conditions and recycling design, the reaction efficiency and product purity are improved.
The efficient synthesis of ethyl 3-ethoxypropionate is achieved, the catalyst is easy to recycle, has high activity, few by-products, high product yield and high purity, which reduces production costs.
Smart Images

Figure CN119552079A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of organic synthesis, and in particular to a high-efficiency synthesis method of ethyl 3-ethoxypropionate. Background Art
[0002] Ethyl 3-ethoxypropionate (EEP, chemical formula: C7H 14 O3, boiling point 169-171℃). EEP is a green and environmentally friendly high-boiling point ester electronic solvent. Compared with similar solvents, it has the advantages of lower surface tension, high resistivity, low volatility, low odor, and green environmental protection. It is mainly used in optoelectronics, aerospace, shipbuilding, automobile, electronic coatings industries, and in the pharmaceutical industry.
[0003] EEP is an important formula component of color photoresist, a key material for the preparation of optoelectronic LCD-TFT color filters CF. It is an upstream key material link in the LCD industry chain. High-purity electronic-grade EEP is also used in the optoelectronic industry for photoresist removal, IC, semiconductor, and circuit board cleaning, completely replacing highly toxic glycol ether solvents. Summary of the invention
[0004] The invention aims to provide an efficient synthesis method of ethyl 3-ethoxypropionate, which has the advantages of simple preparation method, high efficiency, low cost, easy recycling of catalyst, high catalytic activity, high product yield, few by-products, high product purity and broad application prospect.
[0005] The technical solution of the present invention is achieved in this way: The invention provides a high-efficiency synthesis method of ethyl 3-ethoxypropionate. A solid bed is filled with a catalyst, a mixture of ethyl acrylate and anhydrous ethanol is introduced from the bottom for reaction, materials coming out from the top are introduced into a distillation tower for rectification through a filter screen, ethyl 3-ethoxypropionate is obtained and enters a packaging tank, and excess anhydrous ethanol and a small amount of ethyl acrylate and ethyl 3-ethoxypropionate are introduced into a batching tank for cyclic reaction.
[0006] As a further improvement of the present invention, the feeding amount of ethyl acrylate is 1-3 t / h, the molar ratio of ethanol to ethyl acrylate is 5-7:1; and the reaction temperature is 28-80°C.
[0007] As a further improvement of the present invention, the preparation method of the catalyst is as follows: S1. zirconium tetrachloride and terephthalic acid are added to a solvent, ultrasonically dispersed, hydrothermally reacted, centrifuged, washed, and dried to obtain UiO-66; S2. UiO-66 was added to water, dopamine hydrochloride and a catalyst were added, heated and stirred for reaction, centrifuged, washed, and dried to obtain modified UiO-66; S3. The modified UiO-66 was added to the graphene oxide aqueous dispersion, ultrasonically dispersed uniformly, and spray dried to obtain wrinkled graphene oxide-coated modified UiO-66; S4. adding wrinkled graphene oxide coated modified UiO-66, phytic acid, β-cyclodextrin, and potassium dihydrogen phosphate into water, performing a hydrothermal reaction, centrifuging, adding the product into an alkaline solution, stirring the reaction, centrifuging, washing, and drying to obtain β-cyclodextrin-phytic acid-wrinkled graphene oxide coated modified UiO-66; S5. Potassium oxide and β-cyclodextrin-phytic acid-wrinkled graphene oxide-coated modified UiO-66 were mixed evenly and ball-milled to obtain a catalyst.
[0008] As a further improvement of the present invention, the mass ratio of zirconium tetrachloride and terephthalic acid in step S1 is 13-16:10-13, the solvent is a mixed liquid of DMF and acetic acid in a volume ratio of 35-40:3-4, the temperature of the hydrothermal reaction is 120-130°C, and the time is 20-24h.
[0009] As a further improvement of the present invention, the mass ratio of UiO-66, dopamine hydrochloride and catalyst in step S2 is 10:3-5:0.5-1, the catalyst is a Tris-HCl solution with a pH of 9-10, the temperature of the heating and stirring reaction is 45-55° C., and the time is 3-5 h.
[0010] As a further improvement of the present invention, the concentration of the graphene oxide aqueous dispersion in step S3 is 0.5-1 mg / mL, and the solid-liquid ratio of the modified UiO-66 and the graphene oxide aqueous dispersion is 1:3-5 g / mL.
[0011] As a further improvement of the present invention, the mass ratio of the wrinkled graphene oxide coated modified UiO-66, phytic acid, β-cyclodextrin, and potassium dihydrogen phosphate in step S4 is 12-15:3-4:6-8:0.4-0.7, the temperature of the hydrothermal reaction is 150-160°C, the time is 9-11h, the alkali solution is 10-20wt% NaOH, and the stirring reaction time is 1-2h.
[0012] As a further improvement of the present invention, in step S5, the mass ratio of potassium oxide to β-cyclodextrin-phytic acid-corrugated graphene oxide coated modified UiO-66 is 3-4:10, and the ball milling time is 1-3h.
[0013] The present invention further protects a method for preparing the above catalyst, comprising the following steps: S1. 13-16 parts by weight of zirconium tetrachloride and 10-13 parts by weight of terephthalic acid are added to a solvent, ultrasonically dispersed, heated to 120-130°C, hydrothermally reacted for 20-24h, centrifuged, washed, and dried to obtain UiO-66; The solvent is a mixed liquid of DMF and acetic acid in a volume ratio of 35-40:3-4; S2. Add 10 parts by weight of UiO-66 to water, add 3-5 parts by weight of dopamine hydrochloride and 0.5-1 parts by weight of a catalyst, heat to 45-55°C, stir to react for 3-5h, centrifuge, wash, and dry to obtain a modified UiO-66; The catalyst is a Tris-HCl solution with a pH of 9-10; S3. The modified UiO-66 was added to 0.5-1m parts by weight / mL of graphene oxide aqueous dispersion, ultrasonically dispersed uniformly, and spray dried to obtain wrinkled graphene oxide-coated modified UiO-66; The solid-to-liquid ratio of the modified UiO-66 and graphene oxide aqueous dispersion is 1:3-5 parts by weight / mL; S4. 12-15 parts by weight of wrinkled graphene oxide coated modified UiO-66, 3-4 parts by weight of phytic acid, 6-8 parts by weight of β-cyclodextrin, and 0.4-0.7 parts by weight of potassium dihydrogen phosphate are added to water, and hydrothermally reacted at 150-160° C. for 9-11 hours, centrifuged, and the product is added to 10-20wt% NaOH, stirred for reaction for 1-2 hours, centrifuged, washed, and dried to obtain β-cyclodextrin-phytic acid-wrinkled graphene oxide coated modified UiO-66; S5. 3-4 parts by weight of potassium oxide and 10 parts by weight of β-cyclodextrin-phytic acid-wrinkled graphene oxide-coated modified UiO-66 were uniformly mixed and ball-milled for 1-3 hours to obtain a catalyst.
[0014] The present invention further protects a catalyst prepared by the above preparation method.
[0015] The present invention has the following beneficial effects: The industrial production of EEP mainly adopts the base-catalyzed addition reaction of ethyl acrylate (EA) and ethanol, and the commonly used catalysts are sodium ethoxide and strong alkaline anion exchange resin. The sodium ethoxide catalysis method is relatively economical, but the sodium ethoxide needs to be destroyed after the reaction, and a large amount of salt-containing wastewater is generated; the anion exchange resin has poor high temperature resistance, and the reaction temperature must be controlled below 35°C. The present invention prepares a catalyst, which not only has the advantages of large specific surface area, a relatively wide alkalinity range and a simple preparation method, but also has high activity, and the active components are not easy to lose, the K element loading capacity is large, and the firmness is good, and the obtained 3-ethoxypropionic acid ethyl ester has high yield and high purity.
[0016] The present invention prepares a metal organic framework UiO-66, which has a large specific surface area and abundant catalytic active sites. It is a crystalline material formed by metal ions or clusters and organic ligands connected to each other through coordination bonds. Its highly controllable pore structure and surface functional groups provide an ideal platform for catalysis. The surface is modified by coating with dopamine hydrochloride. Compared with the directly prepared UiO-66-NH2 material, the coated amino loading is greater, and it also has more polar active groups, which is easy to load with graphene oxide. The wrinkled structure obtained by spray drying further increases the specific surface area of the carrier and enriches the catalytic active sites. At the same time, the hydroxyl groups on the surface of graphene oxide can be coupled with beta-cyclodextrin through phytic acid, so that the surface is rich in hydroxyl groups, amino groups, phosphate groups, cavities, etc., which are convenient for the adsorption and fixation of the K element and have good firmness, so that in the catalytic process, it is not easy to cause the loss of K after the fluid passes through, the catalyst can be reused, and it still maintains a high activity after repeated reuse, which reduces the reaction cost and does not produce by-products. At the same time, it can also adsorb and fix organic matter, colloids, heavy metal ions, etc. in the raw materials, so that the obtained 3-ethoxypropionic acid ethyl ester has a high yield and high purity, and has broad application prospects.
[0017] The preparation method of ethyl 3-ethoxypropionate is simple, efficient, low in cost, easy to recycle the catalyst, high in catalytic activity, high in product yield, few in by-products, high in product purity, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0019] Figure 1 The present invention is a schematic flow diagram of an efficient synthesis method of ethyl 3-ethoxypropionate. DETAILED DESCRIPTION
[0020] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0021] Graphene oxide aqueous dispersion, 0.5 mg / mL, was purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.
[0022] Preparation Example 1 Preparation of Catalyst Here’s how: S1. 13 g zirconium tetrachloride and 10 g terephthalic acid were added to 200 mL solvent, ultrasonically dispersed at 1000 W for 10 min, heated to 120 ° C, hydrothermally reacted for 20 h, centrifuged, washed, and dried to obtain UiO-66; The solvent is a mixed liquid of DMF and acetic acid in a volume ratio of 35:3; S2. 10 g of UiO-66 was added to 200 mL of water, 3 g of dopamine hydrochloride and 0.5 g of catalyst were added, heated to 45 ° C, stirred for 3 h, centrifuged, washed, and dried to obtain modified UiO-66; The catalyst is a Tris-HCl solution with a pH of 9; S3. 10 g of modified UiO-66 was added to 30 mL of 0.5 mg / mL graphene oxide aqueous dispersion, ultrasonically dispersed at 1000 W for 10 min, and spray dried to obtain wrinkled graphene oxide-coated modified UiO-66; S4. 12 g of wrinkled graphene oxide coated modified UiO-66, 3 g of phytic acid, 6 g of β-cyclodextrin, and 0.4 g of potassium dihydrogen phosphate were added to 200 mL of water, and hydrothermally reacted at 150° C. for 9 h, centrifuged, and the product was added to 10 wt % NaOH, stirred for reaction for 1 h, centrifuged, washed, and dried to obtain β-cyclodextrin-phytic acid-wrinkled graphene oxide coated modified UiO-66; S5. 3 g potassium oxide and 10 g β-cyclodextrin-phytic acid-wrinkled graphene oxide-coated modified UiO-66 were mixed evenly and ball-milled for 1 h to prepare a catalyst.
[0023] Preparation Example 2 Preparation of Catalyst Here’s how: S1. 16 g zirconium tetrachloride and 13 g terephthalic acid were added to 200 mL solvent, ultrasonically dispersed at 1000 W for 10 min, heated to 130 ° C, hydrothermally reacted for 24 h, centrifuged, washed, and dried to obtain UiO-66; The solvent is a mixed liquid of DMF and acetic acid in a volume ratio of 40:4; S2. 10 g of UiO-66 was added to 200 mL of water, 5 g of dopamine hydrochloride and 1 g of catalyst, heated to 55 ° C, stirred for 5 h, centrifuged, washed, and dried to obtain modified UiO-66; The catalyst is a Tris-HCl solution with a pH of 10; S3. 10 g of modified UiO-66 was added to 50 mL of 0.5 mg / mL graphene oxide aqueous dispersion, ultrasonically dispersed at 1000 W for 10 min, and spray dried to obtain wrinkled graphene oxide-coated modified UiO-66; S4. 15 g of wrinkled graphene oxide coated modified UiO-66, 4 g of phytic acid, 8 g of β-cyclodextrin, and 0.7 g of potassium dihydrogen phosphate were added to 200 mL of water, and hydrothermally reacted at 160° C. for 11 h, centrifuged, and the product was added to 20 wt % NaOH, stirred for reaction for 2 h, centrifuged, washed, and dried to obtain β-cyclodextrin-phytic acid-wrinkled graphene oxide coated modified UiO-66; S5. 4 g potassium oxide and 10 g β-cyclodextrin-phytic acid-wrinkled graphene oxide-coated modified UiO-66 were mixed evenly and ball-milled for 3 h to obtain a catalyst.
[0024] Preparation Example 3 Preparation of Catalyst Here’s how: S1. 15 g zirconium tetrachloride and 12 g terephthalic acid were added to 200 mL solvent, ultrasonically dispersed at 1000 W for 10 min, heated to 125 ° C, hydrothermally reacted for 22 h, centrifuged, washed, and dried to obtain UiO-66; The solvent is a mixed liquid of DMF and acetic acid in a volume ratio of 37:3.5; S2. 10 g of UiO-66 was added to 200 mL of water, 4 g of dopamine hydrochloride and 0.7 g of catalyst, heated to 50 ° C, stirred for 4 h, centrifuged, washed, and dried to obtain modified UiO-66; The catalyst is a Tris-HCl solution with a pH of 9.5; S3. 10 g of modified UiO-66 was added to 40 mL of 0.5 mg / mL graphene oxide aqueous dispersion, ultrasonically dispersed at 1000 W for 10 min, and spray dried to obtain wrinkled graphene oxide-coated modified UiO-66; S4. 13 g of wrinkled graphene oxide coated modified UiO-66, 3.5 g of phytic acid, 7 g of β-cyclodextrin, and 0.5 g of potassium dihydrogen phosphate were added to 200 mL of water, and hydrothermally reacted at 155° C. for 10 h, centrifuged, and the product was added to 15 wt % NaOH, stirred for reaction for 1.5 h, centrifuged, washed, and dried to obtain β-cyclodextrin-phytic acid-wrinkled graphene oxide coated modified UiO-66; S5. 3.5 g potassium oxide and 10 g β-cyclodextrin-phytic acid-wrinkled graphene oxide-coated modified UiO-66 were mixed evenly and ball-milled for 2 h to obtain a catalyst.
[0025] Comparative Preparation Example 1 Compared with Preparation Example 3, the difference is that step S2 is not performed.
[0026] The details are as follows: S1. 15 g zirconium tetrachloride and 12 g terephthalic acid were added to 200 mL solvent, ultrasonically dispersed at 1000 W for 10 min, heated to 125 ° C, hydrothermally reacted for 22 h, centrifuged, washed, and dried to obtain UiO-66; The solvent is a mixed liquid of DMF and acetic acid in a volume ratio of 37:3.5; S2. 10 g of UiO-66 was added to 40 mL of 0.5 mg / mL graphene oxide aqueous dispersion, ultrasonically dispersed at 1000 W for 10 min, and spray dried to obtain wrinkled graphene oxide-coated UiO-66; S3. 13 g of wrinkled graphene oxide coated UiO-66, 3.5 g of phytic acid, 7 g of β-cyclodextrin, and 0.5 g of potassium dihydrogen phosphate were added to 200 mL of water, and the reaction was carried out at 155 ° C for 10 h. The product was added to 15 wt% NaOH, stirred for 1.5 h, centrifuged, washed, and dried to obtain β-cyclodextrin-phytic acid-wrinkled graphene oxide coated UiO-66; S4. 3.5 g potassium oxide and 10 g β-cyclodextrin-phytic acid-wrinkled graphene oxide-coated UiO-66 were mixed evenly and ball-milled for 2 h to prepare a catalyst.
[0027] Comparative Preparation Example 2 Compared with Preparation Example 3, the difference is that step S3 is not performed.
[0028] The details are as follows: S1. 15 g zirconium tetrachloride and 12 g terephthalic acid were added to 200 mL solvent, ultrasonically dispersed at 1000 W for 10 min, heated to 125 ° C, hydrothermally reacted for 22 h, centrifuged, washed, and dried to obtain UiO-66; The solvent is a mixed liquid of DMF and acetic acid in a volume ratio of 37:3.5; S2. 10 g of UiO-66 was added to 200 mL of water, 4 g of dopamine hydrochloride and 0.7 g of catalyst, heated to 50 ° C, stirred for 4 h, centrifuged, washed, and dried to obtain modified UiO-66; The catalyst is a Tris-HCl solution with a pH of 9.5; S3. 13 g of modified UiO-66, 3.5 g of phytic acid, 7 g of β-cyclodextrin, and 0.5 g of potassium dihydrogen phosphate were added to 200 mL of water, and hydrothermally reacted at 155 ° C for 10 h, centrifuged, and the product was added to 15 wt% NaOH, stirred for 1.5 h, centrifuged, washed, and dried to obtain β-cyclodextrin-phytic acid-modified UiO-66; S4. 3.5 g potassium oxide and 10 g β-cyclodextrin-phytic acid-modified UiO-66 were mixed evenly and ball-milled for 2 h to obtain a catalyst.
[0029] Comparative Preparation Example 3 Compared with Preparation Example 3, the difference is that step S4 is not performed.
[0030] The details are as follows: S1. 15 g zirconium tetrachloride and 12 g terephthalic acid were added to 200 mL solvent, ultrasonically dispersed at 1000 W for 10 min, heated to 125 ° C, hydrothermally reacted for 22 h, centrifuged, washed, and dried to obtain UiO-66; The solvent is a mixed liquid of DMF and acetic acid in a volume ratio of 37:3.5; S2. 10 g of UiO-66 was added to 200 mL of water, 4 g of dopamine hydrochloride and 0.7 g of catalyst, heated to 50 ° C, stirred for 4 h, centrifuged, washed, and dried to obtain modified UiO-66; The catalyst is a Tris-HCl solution with a pH of 9.5; S3. 10 g of modified UiO-66 was added to 40 mL of 0.5 mg / mL graphene oxide aqueous dispersion, ultrasonically dispersed at 1000 W for 10 min, and spray dried to obtain wrinkled graphene oxide-coated modified UiO-66; S4. 13g of wrinkled graphene oxide coated modified UiO-66, 3.5g of phytic acid, 7g of β-cyclodextrin, and 0.5g of potassium dihydrogen phosphate were added to 200mL of water, and hydrothermally reacted at 155°C for 10h. The reaction was centrifuged, and the product was added to 15wt% NaOH, stirred for 1.5h, centrifuged, washed, and dried to obtain β-cyclodextrin-phytic acid-wrinkled graphene oxide coated modified UiO-66, which was the catalyst.
[0031] Test Example 1 The specific surface area and pore structure of the catalysts prepared in Preparation Examples 1-3 of the present invention and Comparative Preparation Examples 1-3 were tested using an ASAP2400 static nitrogen adsorption instrument from Mircomeritics, Inc., USA. The results are shown in Table 1.
[0032] Table 1 Group <![CDATA[Specific surface area (m 2 / g)]]> <![CDATA[Pore volume (cm 3 / g)]]> Preparation Example 1 552 0.507 Preparation Example 2 556 0.509 Preparation Example 3 559 0.512 Comparative Preparation Example 1 527 0.487 Comparative Preparation Example 2 501 0.437 Comparative Preparation Example 3 542 0.495 It can be seen from the above table that the catalysts prepared in Preparation Examples 1-3 of the present invention have larger specific surface areas and pore volumes.
[0033] Example 1 like Figure 1This embodiment provides an efficient synthesis method of ethyl 3-ethoxypropionate. The catalyst in Preparation Example 1 is filled into a solid bed, a mixture of ethyl acrylate and anhydrous ethanol is introduced from the bottom, and the mixture is heated to 70° C. for reaction. The amount of ethyl acrylate introduced is 1 t / h, and the molar ratio of ethanol to ethyl acrylate is 5:1. The material coming out of the top passes through a filter screen and enters a distillation tower for distillation to obtain ethyl 3-ethoxypropionate and enter a packaging tank. Excess anhydrous ethanol and a small amount of ethyl acrylate and ethyl 3-ethoxypropionate enter a batching tank for a cyclic reaction.
[0034] Example 2 like Figure 1 This embodiment provides an efficient synthesis method of ethyl 3-ethoxypropionate. The catalyst of Preparation Example 2 is filled into a solid bed, and a mixture of ethyl acrylate and anhydrous ethanol is introduced from the bottom, and the mixture is heated to 80° C. for reaction. The amount of ethyl acrylate introduced is 3 / h, and the molar ratio of ethanol to ethyl acrylate is 7:1. The material coming out of the top passes through a filter screen and enters a distillation tower for distillation to obtain ethyl 3-ethoxypropionate and enters a packaging tank. Excess anhydrous ethanol and a small amount of ethyl acrylate and ethyl 3-ethoxypropionate enter a batching tank for a cyclic reaction.
[0035] Example 3 like Figure 1 This embodiment provides an efficient synthesis method of ethyl 3-ethoxypropionate. The catalyst of Preparation Example 3 is filled into a solid bed, and a mixture of ethyl acrylate and anhydrous ethanol is introduced from the bottom, and the mixture is heated to 75°C for reaction. The amount of ethyl acrylate introduced is 2 t / h, and the molar ratio of ethanol to ethyl acrylate is 6:1. The material coming out of the top passes through a filter screen and enters a distillation tower for distillation to obtain ethyl 3-ethoxypropionate and enters a packaging tank. Excess anhydrous ethanol and a small amount of ethyl acrylate and ethyl 3-ethoxypropionate enter a batching tank for a cyclic reaction.
[0036] Comparative Example 1 Compared with Example 3, the difference is that the catalyst is prepared by Comparative Preparation Example 1.
[0037] Comparative Example 2 Compared with Example 3, the difference is that the catalyst is prepared by Comparative Preparation Example 2.
[0038] Comparative Example 3 Compared with Example 3, the difference is that the catalyst is prepared by Comparative Preparation Example 3.
[0039] Test Example 2 The reaction time of 5 h in Examples 1-3 and Comparative Examples 1-3 was evaluated. The results are shown in Table 2.
[0040] Table 2 Group Yield of 3-ethoxypropionic acid ethyl ester (%) Purity of ethyl 3-ethoxypropionate (%) Example 1 99.92 >99.99 Example 2 99.94 >99.99 Example 3 99.97 >99.99 Comparative Example 1 96.73 97.83 Comparative Example 2 94.18 95.39 Comparative Example 3 92.33 90.15 It can be seen from the above table that the methods in Examples 1-3 of the present invention can obtain high-purity ethyl 3-ethoxypropionate with a high reaction yield.
[0041] Test Example 3 After the reactions in Examples 1-3 of the present invention and Comparative Examples 1-3 were continued for 50 hours, evaluation was performed again. The results are shown in Table 3.
[0042] Table 3 Group Yield of 3-ethoxypropionic acid ethyl ester (%) Purity of ethyl 3-ethoxypropionate (%) Example 1 99.89 >99.99 Example 2 99.91 >99.99 Example 3 99.94 >99.99 Comparative Example 1 93.10 94.48 Comparative Example 2 91.47 92.07 Comparative Example 3 90.29 85.78 It can be seen from the above table that in the methods of Examples 1-3 of the present invention, the catalyst can still maintain a relatively high activity after a relatively long catalytic period, which shows that the loss of K is relatively small.
[0043] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. An efficient synthesis method of ethyl 3-ethoxypropionate, characterized in that, The catalyst is filled into the solid bed, and a mixture of ethyl acrylate and anhydrous ethanol is introduced from the bottom for reaction. The material coming out from the top passes through a filter screen and enters a distillation tower for distillation to obtain ethyl 3-ethoxypropionate which enters a packaging tank. Excess anhydrous ethanol and a small amount of ethyl acrylate and ethyl 3-ethoxypropionate enter a batching tank for a cyclic reaction.
2. The synthesis method according to claim 1, characterized in that The amount of ethyl acrylate introduced is 1-3 t / h, the molar ratio of ethanol to ethyl acrylate is 5-7:1; and the reaction temperature is 28-80°C.
3. The synthesis method according to claim 1, characterized in that The preparation method of the catalyst is as follows: S1. zirconium tetrachloride and terephthalic acid are added to a solvent, ultrasonically dispersed, hydrothermally reacted, centrifuged, washed, and dried to obtain UiO-66; S2. UiO-66 was added to water, dopamine hydrochloride and a catalyst were added, heated and stirred for reaction, centrifuged, washed, and dried to obtain modified UiO-66; S3. The modified UiO-66 was added to the graphene oxide aqueous dispersion, ultrasonically dispersed uniformly, and spray dried to obtain wrinkled graphene oxide-coated modified UiO-66; S4. adding wrinkled graphene oxide coated modified UiO-66, phytic acid, β-cyclodextrin, and potassium dihydrogen phosphate into water, performing a hydrothermal reaction, centrifuging, adding the product into an alkaline solution, stirring the reaction, centrifuging, washing, and drying to obtain β-cyclodextrin-phytic acid-wrinkled graphene oxide coated modified UiO-66; S5. Potassium oxide and β-cyclodextrin-phytic acid-wrinkled graphene oxide-coated modified UiO-66 were mixed evenly and ball-milled to obtain a catalyst.
4. The synthesis method according to claim 3, characterized in that In step S1, the mass ratio of zirconium tetrachloride to terephthalic acid is 13-16:10-13, the solvent is a mixed liquid of DMF and acetic acid in a volume ratio of 35-40:3-4, the temperature of the hydrothermal reaction is 120-130° C., and the time is 20-24 hours.
5. The synthesis method according to claim 3, characterized in that In step S2, the mass ratio of UiO-66, dopamine hydrochloride and catalyst is 10:3-5:0.5-1, the catalyst is a Tris-HCl solution with a pH of 9-10, the temperature of the heating and stirring reaction is 45-55° C., and the time is 3-5 hours.
6. The synthesis method according to claim 3, characterized in that The concentration of the graphene oxide aqueous dispersion in step S3 is 0.5-1 mg / mL, and the solid-to-liquid ratio of the modified UiO-66 and the graphene oxide aqueous dispersion is 1:3-5 g / mL.
7. The synthesis method according to claim 3, characterized in that In step S4, the mass ratio of the wrinkled graphene oxide coated modified UiO-66, phytic acid, β-cyclodextrin, and potassium dihydrogen phosphate is 12-15:3-4:6-8:0.4-0.7, the temperature of the hydrothermal reaction is 150-160°C, the time is 9-11h, the alkali solution is 10-20wt% NaOH, and the stirring reaction time is 1-2h.
8. The synthesis method according to claim 3, characterized in that In step S5, the mass ratio of potassium oxide to β-cyclodextrin-phytic acid-wrinkled graphene oxide coated modified UiO-66 is 3-4:10, and the ball milling time is 1-3h.